STUDY OF THE COMPOSITION OF RUBBER COMPOSITE MATERIALS AGAINST WEAR AND TEAR AND TENSILE STRENGTH OF MATERIAL RUBBER SIDEWALL ON A CEMENT PATH IN PT. SEMEN TONASA. Tbk - Halik, Abdul; H. Anwar, Nur Rahmah; Gazali, Muhammad (Department of Electrical Engineering, University of Patria Artha, 2017)
This research is a series of research in terms of getting the outside tire material is good. At this peneltian look for the characteristics of rubber compounds based on variations in the composition of the sulfur: 3, 3.5, and 4 phr, called compounds 1, 2 and 3 of his was done to get the tensile strength and keausannya. The method does is to do a test and tensile test of wear, which then conducted benchmarking with a basic compound manufacturer. Rubber materials processed by mixing rubber taken from ala, artificial rubber and rubber kompo manufacturer. The results obtained from tensile testing is testing the tensile thermal variation 1, 2, 3 and compounds the manufacturer to load the smallest average pull on compound 1 with load per unit area of 13.46 N/mm2 or 403.191 N and highest on the compound manufacturer with 18.06 load N/mm2 or 542.493 N. As for the increase of the average length of the smallest thermal variations on 1 of 6.25 mm and the largest manufacturer of compound 13 mm. Judging from the magnitude of the tensile test, thermal variation 3 have results that come close to the factory compound. Testing the wear and tear of a dry path obtained, the manufacturer of the compound has the lowest wear namely 11.667 mm3/s. On the same test, thermal and thermal variation 1 Variation 2 have a high wear value i.e. each mm3/21.667 seconds and 18.333 mm3/s. While thermal variation 3 has a value close to the factory compound wear namely mm3/13.333 seconds. On a wet path testing, the manufacturer of the compound has the lowest wear namely 3.333 mm3/s. On the same test, thermal variation 1 has a high wear and tear that is 10 mm3/s. While the thermal variations 3 and 4 compounds have almost the same wear value i.e. each mm3/6.667 seconds and 5 mm3/s.